2004
DOI: 10.1093/brain/awh152
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and multiple sclerosis (the PRIMS study): clinical predictors of post‐partum relapse

Abstract: The influence of pregnancy in multiple sclerosis has been a matter of controversy for a long time. The Pregnancy in Multiple Sclerosis (PRIMS) study was the first large prospective study which aimed to assess the possible influence of pregnancy and delivery on the clinical course of multiple sclerosis. We report here the 2-year post-partum follow-up and an analysis of clinical factors which might predict the likelihood of a relapse in the 3 months after delivery. The relapse rate in each trimester up to the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

30
416
2
29

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 579 publications
(477 citation statements)
references
References 11 publications
30
416
2
29
Order By: Relevance
“…8 Breastfeeding was also not shown to affect postpartum relapse activity in PRIMS. 4 Data published by Oliveri et al 9 showed that intravenous methylprednisolone (IVMP) reduced magnetic resonance imaging (MRI) activity, defined as the number of contrast-enhancing lesions over a 2-month period. Therefore, we hypothesized that a dose of IVMP in the immediate postpartum period might reduce the risk of relapse.…”
mentioning
confidence: 99%
“…8 Breastfeeding was also not shown to affect postpartum relapse activity in PRIMS. 4 Data published by Oliveri et al 9 showed that intravenous methylprednisolone (IVMP) reduced magnetic resonance imaging (MRI) activity, defined as the number of contrast-enhancing lesions over a 2-month period. Therefore, we hypothesized that a dose of IVMP in the immediate postpartum period might reduce the risk of relapse.…”
mentioning
confidence: 99%
“…There was also no impact of epidural analgesia on relapse. This corresponds with the outcome of the PRIMS study (254 women with MS, C‐sections 43, EOA 42) (Confavreux et al., 1998; Vukusic et al., 2004) showing no significant difference in the rate of relapse between women who underwent epidural analgesia and those who did not. However, this was a secondary outcome of the study and no detailed analysis was provided (Confavreux et al., 1998).…”
Section: Discussionmentioning
confidence: 95%
“…Our study results of postpartum relapses are consistent with data in other studies (Finkelsztejn, Brooks, Paschoal, & Fragoso, 2011; Vukusic et al., 2004) showing the largest number of relapses in the first trimester postpartum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations